2019
DOI: 10.1111/ecog.04564
|View full text |Cite
|
Sign up to set email alerts
|

Aridity, soil and biome stability influence plant ecoregions in the Atlantic Forest, a biodiversity hotspot in South America

Abstract: Our aims were to quantify and map the plant ecoregions of the Atlantic Forest, a biodiversity hotspot that covers ca 150 million ha in eastern South America. We used a data set on the distribution of 4378 shrub and tree species across 711 localities. Plant ecoregions were identified using analyses of species turnover for both species occurrences and relative abundances. We interpolated NMDS axes of compositional variation over the entire the Atlantic Forest extent, and then classified the compositional dissimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 80 publications
(319 reference statements)
4
40
1
Order By: Relevance
“…In contrast to that has been found for a variety of tropical vegetation types and floristic assemblages (e.g. Cantidio & Souza, 2019;Castro-Insua et al, 2018;Linder et al, 2012;Marques et al, 2020;Saiter et al, 2016;Tuomisto et al, 2019), we found rather smooth borders between subregions. This is attributable to the absence of extensive mountain ranges or steep climatic gradients in most of the Amazon extension, as well as to the historical stability of the tropical forest biome in the basin (Costa et al, 2017), which may have allowed for extensive species dispersal.…”
Section: Regional Patternscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to that has been found for a variety of tropical vegetation types and floristic assemblages (e.g. Cantidio & Souza, 2019;Castro-Insua et al, 2018;Linder et al, 2012;Marques et al, 2020;Saiter et al, 2016;Tuomisto et al, 2019), we found rather smooth borders between subregions. This is attributable to the absence of extensive mountain ranges or steep climatic gradients in most of the Amazon extension, as well as to the historical stability of the tropical forest biome in the basin (Costa et al, 2017), which may have allowed for extensive species dispersal.…”
Section: Regional Patternscontrasting
confidence: 99%
“…We also investigated the relationships of the identified subregions with environmental, historical and human correlates. Our results contribute to the global effort of mapping terrestrial subregions (Cantidio & Souza, 2019;Dinerstein et al, 2017;Moura et al, 2016;Olson et al, 2001;Saiter et al, 2016;Silva & Souza, 2018a) and for conservation planning in the Amazon domain.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations